Engineering novel stabilizers for Pickering nanoemulsions: The role of ultrasonic modification in pea protein-chitosan complexes - Nita Aryanti; Alifia Rizki Adina; Aininu Nafiunisa; Dyah Hesti Wardhani (Case Studies in Chemical and Environmental Engineering)
Pickering nanoemulsions are emulsions characterized by superior stability, achieved through the use of stabilizers with enhanced stability and emulsion properties. The utilization of biomaterials such as pea protein presents challenges in the formation of Pickering nanoemulsions due to its inherent hydrophobicity. In this study, we overcome this limitation by structurally modifying pea protein isolate (PPI) via ultrasonication, followed by complexation with chitosan (CH). The PPI-CH 1:1 ratio exhibited exceptionally high storage stability, indicating that the complexation and structural modification of the protein were optimized to the fullest extent. A Pickering nanoemulsion with a droplet size of 247.59 nm was obtained at a 10 % oil fraction, successfully maintaining stability against creaming over a 20-day storage period with an Emulsion Stability Index of 96.7 %. Furthermore, the emulsion demonstrated remarkable stability under extreme pH conditions, thermal stress, and centrifugal forces. High stability and satisfactory Pickering emulsion results indicate that ultrasonic modification has unfolded pea protein, while complexation with chitosan facilitates electrostatic interactions, enhancing the functional properties of PPI. The findings of this research significantly enhance the utility of pea protein as a biomaterial, and its application on a larger scale is poised to benefit both the pharmaceutical and food industries due to its exceptional stability under varying pH, external forces, and thermal conditions.